Clinical Research Progress of Acupuncture and Moxibustion in the Treatment of Postpartum Depression - Qian, Huang; Xia, Liu (Journal of Contemporary Medical Practice, 2025)
Postpartum Depression (PPD) is a common mental disorder among puerperae, which exerts severe impacts on individuals, families, and society. Currently, there is no standard treatment plan for PPD. In recent years, an increasing number of acupuncture and moxibustion therapies have been applied in the treatment of PPD, achieving significant clinical efficacy. This study intends to sort out the clinical studies on acupuncture and moxibustion for PPD, and discuss the clinical efficacy of different acupuncture and moxibustion treatment methods, so as to provide references for clinical practice.